The comparison between conventional and rice ratoon system on soil properties, rice productivity and nutrient status - Muchammad Bima Gegana Sakti; Komariah Komariah; Dwi Priyo Ariyanto; Sumani Sumani; Muhamad Khoiru Zaki; Keigo Noda (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2021)
Ratoon system is a method of rice cultivation that produces new tillers after the mother plant is harvested and is continued by maintaining and caring for the shoots of the mother plant. In Indonesia, SALIBU and SINGGANG, which are types of rice ratooning, have been developed for Sumatra and Java regions, respectively. SALIBU is an innovation or a modification of the rice ratoon system that focuses on maintaining the time of fertigation and cutting of plant height. SINGGANG, on the other hand, is a rice ratoon system in which the management of fertigation and cutting is not considered. Both systems have not yet been implemented outside their places of origin. This study aims to compare the conventional and modified rice ratoon systems considering parameters such as soil properties, nutrient uptake, and the growth and yield of rice. The effects of rice ratoon systems (SALIBU and SINGGANG,), soil types (Inceptisols, Alfisols, and Vertisols), and cultivars (Pandan Wangi and Mekongga) were evaluated. All treatments were evaluated in a completely randomized design with three replicates in the net house. The results showed that the soil porosity in SINGGANG (48.89%) and SALIBU (46.78%) systems was higher than the conventional system (43.17%) in the Inceptisol soil and Pandan Wangi cultivars. Moreover, SINGGANG had a positive effect on the physical properties of soil (porosity and permeability); whereas, SALIBU had a positive effect on the chemical properties of soil (pH and organic carbon). In contrast, the agronomic parameters showed that the weights of dry matter and dry yield for SINGGANG were 44.96 and 23.09 g per plant clump, respectively, while those for SALIBU were 55.54 and 25.74 g per plant clump, respectively. These were lower than the conventional system (63.18 and 31.21 g per plant clump, respectively). Thus, we concluded that the SINGGANG and SALIBU ratoon systems had a positive impact on soil properties, but both systems could not promote higher rice production than the mother plant in all soil types and cultivars.